Faunal Diversity and Distribution of Hygrobatidae Koch, 1842 Species (Acari: Hydrachnidia) of Turkey and Three Neighboring Countries - Gülle, Pınar; Erman, Orhan; Boyacı, Yunus Ömer (My University, 2021)
This study is aimed to determine the distributions, habitats, and endemism rates of Hygrobatidae species of Turkey andthree neighboring countries. Similarity calculations were made between Turkey and three neighboring countries using theBray-Curtis index. As a result, it has been determined that Turkey has a high of similarity with Greece and Bulgaria and alow index of similarity with Iran. Additionally, a new record, Atractides (Tympanomegapus) lacustris (Lundblad, 1925), hasbeen given for the fauna of Turkey. The number of Hygrobatidae species has been reached 55 with A. lacustris andHygrobatidae species have been recorded from 21 provinces in Turkey.
Keywords: Biyoloji; Deniz ve Tatlı Su Biyolojisi; Zooloji